Building envelope design for climate change mitigation: a case study of hotels in Greece. Issue 10 (25th November 2016) - Farrou, I.; Kolokotroni, M.; Santamouris, M.
Abstract : This paper presents results of a study of the impact of future climate change scenarios as developed by the Intergovernmental Panel on Climate Change and implemented in weather files for specific future time slices (2020, 2050 and 2080) for the three climatic regions of Greece on the design of the external envelope of a hotel building in Greece. The impact of climate change on the hotel is assessed via hourly simulations of a calibrated model developed using the software TRNSYS. Additionally, the paper aims to identify optimal refurbishment strategies, given the constraints of the existing case-study building when transposed to the three different climatic zones in Greece. Two modes of the hotel building were studied: 'all year' and 'seasonally' operated. It was found that different external envelope energy-efficient strategies can be applied depending on the climatic zone and whether the hotel is all-year or seasonally operated.